Causality Analysis of Producer Price Index (PPI) and Consumer Price Index (CPI) in Indonesia - Debby Anggraeni; Tony Irawan (IPB University, 2018)
This study aims to investigate the relationship between PPI inflation and CPI inflation in Indonesia both in general and for each group of commodity, and to identify whether PPI inflation can be a leading indicator for CPI inflation or vice versa. This study employs Granger causality based on VAR model for monthly data series from January 2010 until August 2016. The results show that there are unidirectional relationship between PPI inflation and CPI inflation generally, bidirectional relationship from PPI inflation to CPI inflation for foodstuffs group, unidirectional from CPI inflation to PPI inflation for clothing group, and no causality between PPI inflation and CPI inflation for processed food, beverage, cigarette, and tobacco group.Keywords: Granger causality, producer price index, consumer price index, VAR JEL classification: E31, C22